Two-photon interference with continuous-wave multi-mode coherent light - Kim, Yong-Su; Slattery, Oliver; Kuo, Paulina S.; Tang, Xiao (OPTICAL SOC AMER, 2014)
We report two-photon interference with continuous-wave multi-mode coherent light. We show that the two-photon interference, in terms of the detection time difference, reveals two-photon beating fringes with the visibility V = 0.5. While scanning the optical delay of the interferometer, Hong-Ou-Mandel dips or peaks are measured depending on the chosen detection time difference. The HOM dips/peaks are repeated when the optical delay and the first-order coherence revival period of the multi-mode coherent light are the same. These results help to understand the nature of two-photon interference and also can be useful for quantum information science. (C) 2014 Optical Society of America
Keywords: DIODE-LASER; TIME; PHOTON